Lasioglossins LLIII affect the morphogenesis of Candida albicans and reduces the duration of experimental vaginal candidiasis in mice. (24th October 2017) - Vrablikova, Alena; Czernekova, Lydie; Cahlikova, Romana; Novy, Zbynek; Petrik, Milos; Imran, Saima; Novak, Zdenek; Krupka, Michal; Cerovsky, Vaclav; Turanek, Jaroslav; Raska, Milan
ABSTRACT: Lasioglossins are a group of peptides with identified antimicrobial activity. The inhibitory effects of two synthetic lasioglossin derivatives, LLIII and D‐isomeric variant LLIII‐D, on morphological changes in Candida albicans in vitro and the effect of local administration of LLIII during experimental murine candidiasis were investigated. C. albicans blastoconidia were grown in the presence of lasioglossin LLIII or LLIII‐D at concentrations of 11.5 μM and 21 μM, respectively, for 1, 2 and 3 days and their viability determined by flow cytometry using eosin Y staining. Morphological changes were examined by light and fluorescent microscopy. The Candida ‐inhibitory effect of daily intravaginal administration of 0.7 or 1.4 μg of LLIII was assessed in mice with experimentally‐induced vaginal candidiasis. LLIII and LLIII‐D lasioglossins exhibited candidacidal activity in vitro (>76% after 24 hr and >84% after 48 hr of incubation). After 72 hr incubation of Candida with low concentration of lasioglossins, an increase in viability was detected, probably due to a Candida antimicrobial peptides evasion strategy. Furthermore, lasioglossins inhibited temperature‐induced morphotype changes toward hyphae and pseudohyphae with sporadic occurrence of atypical cells with two or enlarged nuclei, suggesting interference with mitosis or cytokinesis. Local application of LLIII reduced the duration of experimental candidiasis with no evidence of adverse effects. Lasioglossin LLIII is a promising candidate for development as an antimicrobial drug for treating the vaginal candidiasis.